THE INFLUENCE OF THE PRINCIPAL'S VISIONARY LEADERSHIP AND SCHOOL CULTURE ON TEACHER WORK DISCIPLINE IN MUHAMMADIYAH HIGH SCHOOL - RAIS, Qasthoni (Journal of Education and Leadership in Education, 2023)
This research generally aims to analyze, test and determine the influence of the principal's visionary leadership and school culture on the work discipline of Muhammadiyah High School teachers in South Jakarta. Quantitative research method with data collection techniques using questionnaires. The method used is path analysis. The population in this study were Muhammadiyah high school teachers in South Jakarta. The population of this study was 146 teachers consisting of 3 Muhammadiyah high schools in South Jakarta. The research results can be concluded that there is a positive and significant influence of Visionary Leadership (X1) on Work Discipline (X3) 3.1 = 0.304 (30.4%), there is a positive and significant influence of School Culture (X2) on Work Discipline (X3) 3.2 = 0.242 (24.2%), there is a positive and significant influence of Visionary Leadership (X1) on School Culture (X2) 2.1 = 0.495 (49.5%). Based on these results, there is an influence of Visionary Leadership on Teacher Work Discipline in Muhammadiyah High Schools throughout South Jakarta, there is an influence of School Culture on Teacher Work Discipline in Muhammadiyah High Schools in South Jakarta, and there is an influence of Visionary Leadership on School Culture in Muhammadiyah High Schools in South Jakarta.